ARTIFICIAL INTELLIGENCE INTEGRATION IN ENGLISH LANGUAGE LEARNING: A TPACK-BASED CASE STUDY OF SENIOR HIGH SCHOOL ENGLISH TEACHERS IN KARAWANG, INDONESIA - Sumarta; Fauzi Miftakh; Acep Bahrum Kamil3; Fela Dafitri (STKIP Paracendekia NW Sumbawa, 2026)
This study investigates the integration of Artificial Intelligence (AI) in English language learning within the Technological Pedagogical Content Knowledge (TPACK) framework among teachers at Ciampel Senior High School, Karawang Regency, Indonesia. Employing a qualitative case study approach, data were collected through in-depth interviews, surveys, and classroom observations involving five English teachers. Thematic analysis was utilized to identify emerging patterns and themes from the data. The findings revealed three significant results: (1) teachers demonstrated considerable interest in AI integration but encountered substantial challenges in technological knowledge (TK) and technological pedagogical knowledge (TPK) domains; (2) the primary obstacles included inadequate technological infrastructure, insufficient professional development programs, limited school policy support, and concerns regarding academic integrity; and (3) contextually appropriate AI-assisted learning designs must account for teachers' digital literacy levels and available resources. This study contributes to the growing body of literature on AI integration in English as a Foreign Language (EFL) contexts, particularly in under-resourced educational settings.